A derivatization and validation strategy for determining the spatial localization of endogenous amine metabolites in tissues using MALDI imaging mass spectrometry - Manier, M. Lisa; Spraggins, Jeffrey M.; Reyzer, Michelle L.; Norris, Jeremy L.; Caprioli, Richard M. (Journal of mass spectrometry., 2014)
Imaging mass spectrometry (IMS) studies increasingly focus on endogenous small molecular weight metabolites and consequently bring special analytical challenges. Since analytical tissue blanks do not exist for endogenous metabolites, careful consideration must be given to confirm molecular identity. Here, we present approaches for the improvement in detection of endogenous amine metabolites such as amino acids and neurotransmitters in tissues through chemical derivatization and matrix‐assisted laser desorption/ionization (MALDI) IMS. Chemical derivatization with 4‐hydroxy‐3‐methoxycinnamaldehyde (CA) was used to improve sensitivity and specificity. CA was applied to the tissue via MALDI sample targets precoated with a mixture of derivatization reagent and ferulic acid as a MALDI matrix. Spatial distributions of chemically derivatized endogenous metabolites in tissue were determined by high‐mass resolution and MSn IMS. We highlight an analytical strategy for metabolite validation whereby tissue extracts are analyzed by high‐performance liquid chromatography (HPLC)‐MS/MS to unambiguously identify metabolites and distinguish them from isobaric compounds. Copyright © 2014 John Wiley & Sons, Ltd.